Risk management for the development of critical systems projects - Aleman Zambrano, Guillermo José (2022)
Today we can find different critical systems in different fields such as health, military, space, security, etc., where the lives and economy of many people are in danger due to the consequences that may arise from a failure in these systems. For this reason, it is essential to identify, analyze and treat the risks related to critical systems projects and typical risk management processes. In this article, we show and explore different techniques and models applied in different environments, such as medicine and the military field, recognizing concepts and similarities in critical systems and risk management. Finally, determining that there are no defined methodologies for risk management in these systems, in many cases necessary to apply hybrid and dynamic options.